A Study on Awareness, Nutritional Knowledge, and Milk Product Consumption Patterns among Students of Anand and Vidyanagar City - , Dhruvi R. Solanki, M.C. Prajapati, A.K. Makwana, M.D. Gurjar, K.C. Kamani (Archives of Current Research International, 2025)
The present study investigates the awareness, nutritional knowledge, and consumption patterns of milk and dairy products among students in Anand and Vidyanagar, Gujarat. A structured web-based survey was conducted in February 2023 with a sample of 100 students aged 18–26 years, representing a diverse range of academic institutions. The study aimed to assess students’ general awareness of milk’s nutritional benefits, their detailed understanding of milk composition (including fat, SNF, and other components), and their actual consumption behaviors. Results revealed that 87% of students consume milk, with a strong preference for packed milk (79%) over loose milk (51%), and Amul as the most trusted brand (86%). While 77% of respondents recognized milk’s nutritional value, detailed knowledge remained limited, with only 27% aware of specific nutrients like minerals, lipids, and sugars. Daily milk consumption was reported by 57% of students, primarily in the morning (76%), with Gold (6% fat) and buffalo milk being the preferred variants. Additionally, 95% of students consumed milk-based products, with high demand for traditional items such as curd, buttermilk, and paneer. Motivations for milk consumption were largely health-driven (60%) or habitual (32%), while non-consumption was primarily due to taste aversion or veganism. The findings underline a positive attitude towards dairy consumption among youth but highlight gaps in detailed nutritional literacy. These insights can inform targeted nutrition education programs and help stakeholders in the dairy sector align product offerings with consumer needs.